STATISTICAL ANALYSIS OF H.264/AVC DEBLOCKING FILTER - Raja, G. (The Nucleus, 2012)
The latest video coding standard, H.264/AVC uses in-loop deblocking filter for suppression of blocking artifacts at low bit rates. The deblocking filter can effectively suppress the blocking artifacts due to low bit rate video coding, however it is highly computationally complex. This paper describes statistical analysis of H.264/AVC deblocking filter for various QCIF sequences. The deblocking filtering phenomenon can be divided into two steps: decision to apply filter (no filter/strong filter/normal filter) and application of filter. Number of operations: additions, shifts and comparisons spent in deblocking filter are measured. Moreover, frequency of usage of strong and normal filter for various video sequences is computed. It has been found that 88.49% of average number of operations is spent to take decision about type of filter (no filter/normal filter/strong filter) whereas11.51% of average number of operations is spent for filtering of samples for various QCIF video sequences.